A history of Luther seminary : 1869-2019 - Granquist, Mark Alan, 1957- (Fortress Press, 2019)
Church historian and Luther faculty member Mark Granquist provides a new and comprehensive history of Luther Seminary just in time for the celebration of the institution's 150th anniversary (1869-2019). It also explores recent history, analyzes the challenges faced by the ELCA, and the major shifts in theological education in the early 21st century, and includes a gallery of photos chronicling Luther's history.